PENGANTAR TEOLOGI PENTAKOSTA (INTRODUCTION TO PENTECOSTAL THEOLOGY) - Bobby Kurnia Putrawan (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2019)
Abstract The Pentecostal Church was originally thought to be a movement. It is said to be a movement, because at first the Pentecostal church emphasized life experiences. Seeing this, the theologians say that the Pentecostal church does not have a theology which is, how theology is christian, logical, and systematic. In later developments, the Pentecostal church was accepted among denominations of Christian churches in general and standardized the doctrines of the Pentecostal church in the form of Pentecostal theology. So that Pentecostal theology can be taught and studied by Pentecostal people and denominations of non-Pentecostal churches. In this article, the author brings up some of the core thoughts of Pentecostal theology, namely the Bible, the living and true God, salvation, baptism, tongues, holy communion, holiness of life and holistic behavior, divine healing, eschatology, church, and worship and liturgy. Keyword: introduction, teologi, pantekosta Abstrak Gereja Pantekosta pada awalnya dianggap adalah suatu gerakan. Dikatakan gerakan, karena pada awalnya gereja Pantekosta menekankan pada pengalaman hidup. Melihat hal ini, sebagai teolog mengatakan bahwa gereja Pantekosta tidak memiliki teologi yang yang, bagaimana teologi itu kristis, logis, dan tersistematis. Dalam perkembangan kemudian, gereja Pantekosta diterima di kalangan denominasi gereja-gereja Kristen pada umumnya dan membakukan doktrin-doktrin gereja Pantekosta dalam bentuk teologi Pantekosta. Sehingga teologi Pantekosta dapat diajarkan dan dipelajari oleh kalangan umat Pantekosta dan denominasi gereja-gereja non-Pantekosta. Dalam artikel ini, penulis mengangkat beberapa pemikiran inti dari teologi Pantekosta, yaitu Alkitab, Allah yang hidup dan benar, keselamatan, baptisan, bahasa lidah, perjamuan kudus, kesucian hidup dan perilaku yang menyeluruh, kesembuhan ilahi, eskatologis, gereja, serta ibadah dan liturgi. Kata kunci: pengantar, teologi, pantekosta